Pref-1, a Gatekeeper of Adipogenesis - Hudak, Carolyn S.; Sul, Hei Sook (Frontiers in Endocrinology, 2013)
Preadipocyte factor 1 (Pref-1, also called Dlk1/ FA1) is a molecular gatekeeper of adipogenesis by maintaining preadipocyte state and preventing adipocyte differentiation. Pref-1 is made as an epidermal growth factor-like repeat containing transmembrane protein, and is cleaved by TNFα-converting enzyme (TACE) to generate a soluble form, which acts as an autocrine/paracrine factor. Pref-1 upregulates Sox9 expression by activating the ERK/MAPK pathway and the Pref-1 interaction with fibronectin is required for inhibition of adipogenesis. Pref-1 also prevents brown adipocyte differentiation and its thermogenic function. Here, we highlight the recent evidence for the role of Pref-1 in adipogenesis.